ANALISIS PENGARUH CURRENT RATIO (CR) NET PROFIT MARGIN (NPM) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BEI TAHUN 2016-2019 - Emelia; Suryadi1, Hasdi (Fekon Uvaya Banjarmasin, 2021)
This study aims to determine and analyze the effect of Current Ratio (CR), Net Profit Margin (NPM) and Earning Per Share (EPS) partially on stock prices in telecommuni-cation companies listed on the IDX. To find out and analyze the effect of Current Ratio (CR), Net Profit Margin (NPM) and Earning Per Share (EPS) simultaneously on the Share Price of telecommunications Companies Listed on the IDX. This is to determine the variables that have a dominant effect on stock prices in telecommunications companies listed on the IDX. This research is a correlational study. This study uses multiple linear regression methods to test hypotheses whit statistical analysis tools in the form of SPSS Version 21 software. Hy-pothesis testing is carried out after the multiple linear regression model to be usaed is deemed feasible or free from violations of classical assumption so that the test results can be interpret-ed appropriately. Classical assumption testing includes normality test, multicollinearity test, autocorrelationtest, heteroscedasticity test. The result of this research show that Current Ratio (CR) has no significant effect on stock princes and Earning Per Share has a significant effect on stock prices in telecommunications companies listed on the Indonesia Stock Exchange in 2016. Until 2019. Current Ratio (CR), Net Profit Margin (NPM) and Earning Per Share sim-ultaneously affect stock prices. The variable that has a dominant influence on share prices in telecommunications companies listed on the Indonesia Stock Exchange for the period 2016 to 2019 is the variable Earning Per Share (EPS).Current Ratio (CR) Net Profit Margin (NPM), Earning Per Share (EPS), Harga Saham